Cellular response to empty and palladium‐conjugated amino‐polystyrene nanospheres uptake: A proteomic study. Issue 1 (January 2015) - Pietrovito, Laura; Cano‐Cortés, Victoria; Gamberi, Tania; Magherini, Francesca; Bianchi, Laura; Bini, Luca; Sánchez‐Martín, Rosario M.; Fasano, Mauro; Modesti, Alessandra
<x xml:space="preserve">Abstract</x> Amino polystyrene nanospheres are shown to be efficient and controllable delivery devices, capable of transporting several bioactive cargoes. Recently, the design of a new device for prodrug activation, using these nanospheres with palladium encapsulated onto them, has been developed successfully. To study the influence of the cellular uptake of these nanodevices, we investigated the cellular response of human embryonic kidney cells (HEK‐293T) and murine fibroblasts (L929) treated with empty or palladium‐conjugated amino polystyrene nanospheres. To identify differentially expressed proteins, we performed an exhaustive proteomic analysis. In accordance with genomic data previously obtained, the uptake of the empty nanospheres did not induce significant variation in protein expression levels. Following the treatment with palladium‐conjugated nanospheres, some changes in protein profiles in both cell lines were observed; these alterations affect proteins involved in cell metabolism and intracellular transport. No key regulator of the cell cycle result was differentially expressed after the treatment, confirming that these innovative drug delivery systems are harmless and well tolerated by the cells.